Uruguay : 2016 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights that Uruguay is demonstrating resilience in the face of recessions in its large neighbors. The economic slowdown has bottomed out in 2016 and there are signs that the economy is on an incipient recovery path. Financial stability risks are limited. Nonperforming loans remain relatively low, at 3.5 percent of total loans, while provisions are high. Real growth is estimated at 1.2 percent in 2016 and projected to reach 1.4 percent in 2017, as the external environment strengthens, together with private consumption.